Obecné požadavky kvality programových dokumentů - Luštický, Martin; Musil, Martin; Kincl, Tomáš; Váchová, Lucie; Zelená, Veronika (Univerzita Pardubice, 2010)
The systematic tourism promotion can be understood as a specific tool of a regional policy of the Czech regions. At the present time almost all regions have disposed of a particular programme document focused on a development of tourism in a given region. Nevertheless these documents are considerably different in the case of their form and content. That is why an evaluation of their quality is quite difficult. One of the reasons of this situation is an absence of the requirements on a quality of these documents. This paper resulted from the methodological concept which aim is to set the basic requirements on the form and content of the programme documents.
Keywords: tourism; regional planning; programme documents; quality; requirements